2019
DOI: 10.1007/s12209-019-00206-x
|View full text |Cite
|
Sign up to set email alerts
|

Gelation Phenomenon During Crystallization of Cefpiramide Sodium

Abstract: Unlike the adverse effect caused by the gelation during crystallization process, gelation of cefpiramide sodium was found to provide ideal product properties, such as a larger and more regular crystal shape. The causes of the gelation phenomenon and the mechanism of gel-crystal transition during the crystallization of cefpiramide sodium were both investigated in this work. The gel was formed due to the strapping of the solvents by the networks of cefpiramide sodium molecules. The whole gel-crystal transition p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…It is found that the gelation phenomenon often occurs in the crystallization process of tilmicosin phosphate, which leads to small particle sizes and easy aggregation. In recent years, there have been reports on the gelation phenomenon and gelation mechanism in the process of drug crystallization. Ouyang et al studied the gel formation and spontaneous crystallization of Valnemulin hydrogen tartrate in a mixed solvent system. The results showed that the gel was formed temporarily and played an intermediate role in the amorphous transformation process.…”
Section: Introductionmentioning
confidence: 99%
“…It is found that the gelation phenomenon often occurs in the crystallization process of tilmicosin phosphate, which leads to small particle sizes and easy aggregation. In recent years, there have been reports on the gelation phenomenon and gelation mechanism in the process of drug crystallization. Ouyang et al studied the gel formation and spontaneous crystallization of Valnemulin hydrogen tartrate in a mixed solvent system. The results showed that the gel was formed temporarily and played an intermediate role in the amorphous transformation process.…”
Section: Introductionmentioning
confidence: 99%
“…Besides, the operation time and difficulty of subsequent drying steps are increased, which affects the product quality. There have been reports on the gelation phenomenon and gelation mechanism in the process of drug crystallization in recent years. Gao et al studied the jelly-like phase state of cefotaxime sodium (CTX) and its spontaneous transformation into crystals by spectroscopy and microscopy monitoring technologies. The experiment indicates that the orientational hydrogen bonding between the solvent and CTX molecule facilitates the construction of the CTX crystal structure.…”
Section: Introductionmentioning
confidence: 99%
“…There are a lot of studies that aim to solve the gelation phenomenon during a crystallization process. , Controlling the solution concentration and associated temperature is a common method to optimize the process to avoid gelation. ,, And another method is seeding-assisted crystallization to initialize the nucleation to avoid gel phase formation. It can induce the crystallization process, and the crystal growing from the crystal nucleus can achieve product consistency, to improve the yield and quality of crystals.…”
Section: Introductionmentioning
confidence: 99%